2018
DOI: 10.1158/1535-7163.mct-17-1107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Next-Generation Sequencing for Precision Oncology in Rare Cancers

Abstract: The European Society for Medical Oncology defines rare cancers as 5 or fewer cases per 100,000 persons per year. For many rare cancers, no standard of care exists, and treatment is often extrapolated. Identifying potentially targetable genomic alterations in rare tumors is a rational approach to improving treatment options. We sought to catalog these mutations in rare tumors and to assess their clinical utility.For this retrospective analysis, we selected rare tumor patients from a dataset of patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
(21 reference statements)
1
22
1
Order By: Relevance
“…The presence of mutations in PIK3CA in nearly 50% of cases suggests that they are not only different to IC‐NST but may also represent a unique subgroup, as the PIK3CA mutation frequency in other BL/TN breast cancers is only ∼8% . Apart from PIK3CA , exome and targeted sequencing studies have revealed frequent mutations in TP53 (69%), PIK3R1 (11%), ARID1A (11%), FAT1 (11%), and PTEN (11%) , and possibly also NOTCH and MCL1 . Interestingly, a very high frequency (97.5%; 39/40) of A14V mutations in ribosomal protein L39 has also been reported in a CAST PCR study , which may have implications for the therapeutic application of nitric oxide synthase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of mutations in PIK3CA in nearly 50% of cases suggests that they are not only different to IC‐NST but may also represent a unique subgroup, as the PIK3CA mutation frequency in other BL/TN breast cancers is only ∼8% . Apart from PIK3CA , exome and targeted sequencing studies have revealed frequent mutations in TP53 (69%), PIK3R1 (11%), ARID1A (11%), FAT1 (11%), and PTEN (11%) , and possibly also NOTCH and MCL1 . Interestingly, a very high frequency (97.5%; 39/40) of A14V mutations in ribosomal protein L39 has also been reported in a CAST PCR study , which may have implications for the therapeutic application of nitric oxide synthase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Rare cancers for which, to our knowledge, comprehensive genomic profiles have not been previously published by The Cancer Genome Atlas (TCGA) (although some have been reported outside of TCGA), include adenoid cystic, anus, neuroendocrine, nonmelanoma skin, salivary gland, small intestine, thyroid, vaginal and vulvar, and unknown primaries (Fig. A‐I).…”
Section: Resultsmentioning
confidence: 99%
“…We also focused on reporting PI3K pathway alterations in rare tumor types, for which few or no studies are available . Overall, PIK3CA continues to be the most frequently altered gene, predominantly in squamous cell histologies, including anal (32%), vulvar (23%), and unknown primary (22%) sites.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting "driver mutations" in cancer is considered an important new approach to therapy that takes into consideration a varied mutational landscape present in tumours, even when arising in the same tissue [34][35][36]. The paradigm set by TKI therapy of CML and ALK inhibition in a small subset of patients with non-small cell lung cancer is quite compelling.…”
Section: Discussionmentioning
confidence: 99%